KEANEKARAGAMAN JENIS KUPU-KUPU DI BEBERAPA TIPE HABITAT DI PONDOK AMBUNG TAMAN NASIONAL TANJUNG PUTING KALIMANTAN TENGAH - Yusi Indriani; Lin Nuriah Ginoga; Burhanuddin Masy'ud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
The study carried out to identify species diversity of butterflies in several typesof habitats in Pondok Ambung, Tanjung Puting National Park Central Kalimantan.The study especically to determine species richness, species diversity, evenness, similarity and correlation between habitat characteristics and species diversity of butterflies. The study were done in eigth types of habitat - lowland forest, swamp forest, peat swamp forest, kerangas (dry-land habitat), grassland, burnt forest, Camp Ambung and nursery camp. One transect along 500 m for every habitat types with sweeping and trapping methods were used to collect and identified of butterflies species. Rambutan and watermelon were used as trap bait. The result showed that a total of 76 butterflies species were identified including five family i.e. Papilionidae (11 species), Pieridae (6 species), Nymphalidae (43 species), Lycaenidae (14 species), and Hesperiidae (2 species). The number of species were different in every habitat types, there are lowland forest 33 species, swamp forest 24 species, peat swamp forest 13 species, kerangas (dry-land habitat) 20 species, grassland 11 species, burnt forest 27 species, Camp Ambung 37 species, and nursery camp 32 species. Result of the study also showed that there were different index of species richness, diversities and similarities of butterflies species in every habitat type, and the correlation between habitat condition and butterflies species diversities especially related to temperature and relative humidity, open area, water source, and vegetation as food plant, shelter, and cover for butterflies. Keywords : butterflies, polinator, species diversity, habitat types, trap bait, national park